Algoritma Perhitungan Charge Occurrence Probability (COP) Pada Data Self Potensial - Muhammad Zuhdi; Syamsuddin Syamsuddin; Bakti Sukrisna (Prodi Fisika FKIP Unram, 2020)
Calculation Algorithm of Occurrence Probability (COP) of Self Potential Data. Self potential is often also called spontaneous potential is one of the geophysical methods that is based on the electrical properties of the material below the earth surface. Self potential arises due to the presence of electric charged of minerals that come in contact with electrolyte solutions around these minerals. Charge Occurrence Probability (COP) is one method of interpreting self potential data. The measurement of self potential on the surface is carried out using two porouspot electrodes made of copper which are immersed in copper sulfate or perusi. The COP calculation algorithm performed in this study is intended for users of the Matlab program. The research algorithm consists of two kinds, namely two-dimensional algorithm and 3-dimensional algorithm. Two-dimensional algorithm is performed on a line in a certain direction through the center of the anomaly. Three-dimensional algorithm is performed by the gridding method which is generated from the 2-dimensional calculation algorithm. Theoretically the resolution generated from this algorithm depends on the density of self potential data. Key Words: Self Potential, Spontaneous, Charge Occurrence Probality, COP